Peran Pembaruan Teknologi Dalam Mengoptimalkan Efisiensi Operasional Di Bidang Manajemen Ekonomi: Tinjauan Kritis Literatur - Abdelina; Lilis Saryani; Ahmad Sayuti Pulungan (Yayasan Perguruan Kampus, 2025)
This research took place at the Padangsidimpuan City Regional Drinking Water Company. The aim that the researcher wants to achieve from the research is to find out how the service quality strategy at Padangsidimpuan City's regional drinking water company improves service quality. This research uses a qualitative approach with the library study method. The data analysis used is qualitative analysis using data reduction, presenting data and drawing conclusions. The informants for this research were 5 people consisting of 2 librarians and 3 members of the general public. The data collection techniques used were observation, interviews and literature study. Based on data analysis of the results of interviews conducted by researchers, it was concluded that by using a combination method, namely online and manual, to improve the quality of consumer service, namely improving the quality of clean water that will be distributed to the community, improving the distribution system for consumers, so that clean water is distributed evenly. to all consumers in the Bontang city area, providing digitalized services to speed up the accessibility and responsiveness of services and trying to be friendly to consumers. However, there are still many obstacles and complaints from consumers/the wider community that the quality of the water supplied is still often cloudy or dirty and smells bad. Water is an indispensable need of society, so the quality of service must be prioritized and the quality of the water must also be maintained so that it is better over time. to time. Even though there are several deficiencies in both water quality and distribution which is often late, as long as water distribution to consumers continues, consumers still hope that the water quality will be better in the future.